Establishment of Repression by Lambdoid Phage in Catabolite Activator Protein and Adenylate Cyclase Mutants of Escherichia coli - Grodzicker, Terri (1972)
Lambdoid phages form clear plaques and show reduced ability to establish immunity in strains of Escherichia coli that lack adenylate cyclase or catabolite activator protein. The absence of the activator protein or cyclic AMP reduces the frequency of lysogenization, but does not prevent steady-state repressor synthesis of a lysogen. Lambda phage mutants able to form turbid plaques on strains that lack catabolite activator protein or adenylate cyclase have been isolated and analyzed.